Metode Profile Matching pada Sistem Pendukung Keputusan Penerima Beasiswa Bantuan Siswa Miskin (BSM) di SMAN 1 Pematang Siantar - Ade Linhar P, Meri Nova Marito Br Sipahutar, Sardo Pardingotan Sipayung (Jurnal Elektronika dan Teknologi Informasi, 2023)
This study aims to develop a decision support system that can facilitate the process of receiving scholarship assistance for poor students. This decision support system uses the calculation method of the profile matching method. This system displays the ranking results of students who meet the criteria for receiving scholarships. The criteria used in this study are academic aspects consisting of semester and class grades, family economic aspects, consisting of parents' occupation, parents' income, number of dependents of parents and children's status. Supporting aspects are organization and non-academic achievements. The decision support system for poor student assistance scholarship recipients helps make decision making easier.